Kampus Hijau Berkelanjutan Dalam Perspektif Pendidikan Lingkungan - Bakaruddin, Bakaruddin; Afriyeni, Afriyeni; Algusri, Jeki (Akuntansi & Ekonomika, 2023)
The purpose of this research was to study literature, relating to a sustainable green campus from the perspective of the UI Green Metric education and research category, and gain an understanding of environmental education to students in higher education. In implementing a green campus, there are three related factors in educational activities, that is; First, the relationship between seminar and education activities practice, which can be done by students or universities. Second, the relationship with the green campus campaign can be managed bay universities and students. Third, relationship with the implementation of green campus activities by reducing paper use, and providing short courses on the environment to communities around the campus. Higher education is a party that has considerable influence in determining policy. Higher education has professionals who have studies in solving a problem in the environment field.